Neurosarcoidosis Presentation as Adipsic Diabetes Insipidus Secondary to a Pituitary Stalk Lesion and Association with Anti-NMDA Receptor Antibodies - Jose Gabriel Solis; Arturo Olascoaga Lugo; Marco Antonio Rodríguez Florido; Bayron Alexander Sandoval Bonilla; Jose Malagón Rangel (Case Reports in Neurological Medicine)
Sarcoidosis is a multisystemic inflammatory disease of unknown cause. It is characterized by the presence of noncaseating granuloma on a biopsy specimen. Clinical presentation varies across case report series with myriad of symptoms ranging from fever, respiratory symptoms, and skin lesions, or atypical symptoms like heart block or neurological symptoms. Hence, we report the case of a 22-year-old woman with encephalitis, a pituitary mass, and adipsic diabetes insipidus. The diagnostic approach did not end on the biopsy of the lesion, which reported noncaseating granulomas; on the contrary, it was the beginning of a path to exclude other causes of the central nervous system granulomas that ended with the diagnosis of the isolated central nervous system sarcoidosis. Also, we report the first proven association between anti-NMDA receptor antibodies and sarcoidosis.